Capital Adequacy, Asset Quality and Banking Sector Performance - IKPESU, FREDRICK; OKE, B.O. (Acta Universitatis Danubius. Œconomica, 2022)
The purpose of this paper is to examine the effect of capital adequacy and asset quality on banking sector performance in Nigeria using annual panel data from the period 2010 to 2019. The study employs the system generalized method of moments (SGMM) in analysing data obtained from audited financial statements of twelve banks listed on the floor of the Nigeria stock exchange for the period 2010 to 2019. The twelve banks used control about 95% share of the market. The outcome of the study revealed that capital adequacy and asset quality both affect bank performance positively in Nigeria. Thus, suggesting that capital adequacy and asset quality enhance and stimulate banking sector performance in the country. Also, the findings of the study indicate that adequate capital and sound asset quality translate to improved earnings and performance of the banks.